Adaptation Strategies and Fishermen's Welfare: Local Wisdom in the Informal Economy in Jaring Halus Village, Langkat - Faozanolo zebua; Nathanael Try Gusmartin Lase; Gibran Muhammad; Sandi Ardiansa Waruwu; Michael haradongan Siallagan (Talenta Publisher, 2026)
Although local wisdom is often romanticized as a pure communal asset, its dual role as both a survival mechanism and an instrument of structural reproduction within the informal economy has rarely been theorized in depth. This study aims to address this research gap by analyzing how local wisdom functions as social capital and a socio-economic adaptation mechanism for informal fishermen in Jaring Halus Village, Langkat. Using a qualitative meta-synthesis approach, this study systematically integrates findings from 25 reputable academic articles to construct a more robust sociological framework. The findings reveal that while local wisdom provides a crucial social safety net—functioning as an informal “community bank” and social insurance, this practice simultaneously reinforces structural inequality through an exploitative patron-client system. Analysis through the lens of Anthony Giddens’s theory of Structuration and Pierre Bourdieu’s Social Capital demonstrates that symbolic capital within local traditions is used to legitimize the dominance of capital owners over fishing laborers. From a development sociology perspective, this study concludes that inclusive coastal development must go beyond normative approaches by critically addressing the power inequalities hidden behind the local wisdom framework in order to achieve multidimensional well-being.